Comparative Study of the Jurisdiction of the Stock Exchange’s Board of Directors in Dealing with Capital Market Disputes in the Laws of Iran, America, and England - Nima Alijannejad; Hamid Abhari; Sam Mohammadi (پژوهشنامه حقوق تطبیقی, 2023)
Note 1, Article 43 of the Securities Market Law, the board of directors of the stock exchange, along with the arbitration board, is competent to deal with damage claims in the process of the initial offering of securities; The board of directors of the stock exchange, in addition to the dignity and duties of the board of directors of public joint-stock companies, has other competences and duties regarding being a publisher and self-regulating organization. The above-mentioned regulation needs to be carefully examined in terms of the type, scope and limits of jurisdiction of the board of directors of the stock exchangeAnd by examining it, it is discovered that it is unclear about the procedure and organization of the hearing, as well as the issuance of the opinion and its implementation. In addition, the board of directors lacks any legal-judicial dignity, and the handling of lawsuits in it is faced with a fundamental problem, and due to the jurisdiction of two authorities with different organizations, the possibility of conflicting opinions issued in a single matter is very high. However, in the laws of other countries, including the United States and the United Kingdom, although other institutions other than the court are responsible for dealing with violations, creating compromises, arbitration between the injured party and the causer of the damage, and similar cases in the process of the initial offer, the judicial investigation of the issue is the responsibility of the judicial system. A detailed examination of the regulations on the topic of discussion and its adaptation to other countries makes clear the necessity of its narrow interpretation, modification and completion in the current situation where the capital market needs support; Therefore, this article aims to emphasize the necessity of amending the relevant regulations by carefully examining the existing internal and external sources and writings, while examining the various aspects of the board of directors' competence;  Especially since the preparations for amending the law have already started.